Anti-windup design for time-delay systems via generalised delay-dependent sector conditions - Chen, Yonggang; Li, Yongmin; Fei, Shumin (IET control theory & applications, 2017)
This study is concerned with the anti-windup design problem for linear time-delay systems with actuator saturation. By utilising the information of the time delay sufficiently, the authors first propose the generalised delay-dependent sector conditions. Then, based on the novel sector conditions, augmented Lyapunov–Krasovskii functionals and several integral inequalities, improved delay-dependent sufficient conditions are established for saturated time-delay systems in terms of linear matrix inequalities, which ensure the existence of the anti-windup gain. Finally, numerical examples demonstrate the effectiveness and the reduced conservatism of the results in this study.